The trend of urbanization in North 24 Parganas District of West Bengal - Rahaman, Mashihur; Panda, Damodar (National Geographical Journal of India, 2022)
In response to the changes in the human and natural environment, developing countries have experienced dramatic urbanization. In this paper, North 24 Parganas district has been taken to understand the changing pattern and the causes of urbanization, its relationship with socio-economic development. The urbanization process has been analyzed for the period 1951-2011 of all the 22 Blocks using the Census of India data. The decadal growth rate of urban population and urban centers are analyzed to study the trend pattern of urbanization. The trend of urbanization in the district shows a different pattern than in the state. Though the share of the urban population and the number of urban centers in the district are the highest in the state, the growth rate of the urban population shows a declining trend. At the Block level, the spatial and temporal pattern of urbanization in the district is highly variable due to socio-economic disparity. The western part of the district shows highly urbanized due to its proximity to the agglomeration and outgrowth of the Kolkata metropolitan Centre.